Does Religiosity Responds to Excessive Consumption? Analysis of Indonesia Family Life Survey 5 - Cinantya Sriyono Putri; Yan Putra Timur; Ilmiawan Auwalin; Sulistya (Indonesian Journal of Islamic Literature and Muslim Society, 2023)
This paper investigates the relationship between Islamic religiosity and excessive conspicuous luxury consumption (israf) in Indonesia, the largest Islamic society in the world. This paper is the first of research projects that examined the relationship between religiosity and israfin the scale of the country. This study uses a probit model estimation model using STATA 12 software. The data set being used is Indonesia Family Life Survey 5 (IFLS5), which consists of a 5.646 Moslem family sample (>20.000 individual Moslems) representing about 83% of the Indonesian population living in 13 of the 26 provinces in Indonesia. This paper examined the relationship between Islamic religiosity (identity religiosity, intrinsic religiosity, extrinsic religiosity) and excessive conspicuous luxury consumption (israf). The result is no relationship between Islamic religiosity and Israf in Indonesia. Identity, intrinsic and extrinsic religiosity insignificantly corresponds to israf. The findings of the paper can be a suggestion for Islam in teachings about israf, which can be more emphasized in the family by the parents, to be included in the school curriculum, and in prayer meetings by the religious leader in order to make having an Islam religiosity can have a significant negative relationship to israf lifestyle.